Perspektif Hukum Ekonomi Syariah Sistem Penyaluran Dana Bank Syariah Pada Masyarakat (Studi Di Desa Sukamulya Lempasing Kecamatan Teluk Pandan Kabupaten Pesawaran) - Devei, Astri; Ilyas, Muhammad; Astuti, Widi (ASAS, 2022)
The development of the bank accompanied by an increasingly advanced model of channeling funds, one of which is carried out by Islamic banks, is one of the solutions to help the community's economy, especially in Sukamulya Lempasing Village. The study focuses on the system and perspective of sharia economic law in the distribution of Islamic bank funds to the community in Suka Mulya Lempasing Village.  The purpose of this study is to find out the system and perspective of Islamic economic law are adopted there.  The study is conducted by field research with data collection, one of which is an interview. Then it is analyzed using descriptive analysis with an inductive thinking approach.  The results of the research can be concluded that the system of channeling funds or Islamic bank financing in Suka Mulya Lempasing Village, Teluk Pandan District, Pesawaran Regency uses financing with a joint liability system (Tanggung Renteng).  From the perspective of sharia economic law, the fund distribution system implemented in Sukamulya Lempasing Village, the system of shared obligations (Tanggung Renteng), is in accordance with the principle of Muamalah, namely Kafalah.  In which a commitment is formed to work together and be responsible between one member to another in the event of arrears of installments by one of the members. Keywords: Sharia Economic Law, Community, Bank Fund Distribution System,